Re-analysis of pluvial precipitation in southern Brazil - Nery, Jonas Teixeira [UNESP]; Carfan, Ana Claudia [UNESP] (Centro Ciencias Atmosfera Unam, 2014)
This study examined precipitation in southern Brazil based on a data set provided by the Brazilian National Water Agency, covering the period from 1976 to 2010. Data were homogenized using the R software and the Climatol subroutine, which allow completing missing data. Isohyets were drawn using the Geostatistics software to obtain a semivariogram for each analysis. There was a remarkable interannual variability in this region, with positive anomalies in the warm phase (El Nino) and negative anomalies in the cold phase (La Nina) of ENSO. Also, the responses of this variability were not uniform in the entire region, since there was variability from year to year and from event to event.

En este estudio se analiza la precipitación en el sur de Brasil con base en un conjunto de datos proporcionados por la Agencia Nacional del Agua de Brasil que abarcan el periodo 1976-2010. Los datos se homogeneizaron usando el software R y la subrutina Climatol, que permite completar la información faltante. Se extrajeron las isoyetas mediante el software Geostatistics para obtener un semivariograma correspondiente a cada análisis. Se observó una variabilidad interanual notable en esta región, con anomalías positivas en la fase caliente (El Niño) y anomalías negativas en la fase fría (La Niña) del fenómeno ENSO. Además, las respuestas de estas variaciones en toda la región no fueron uniformes, ya que se observó variabilidad interanual y entre eventos.
Keywords: Anomalies; Variability; ENSO